The Influence of Individual Counseling Techniques with a Humanistic Approach to Increase Confidence in Children with Disabilities - Samsuddin, Yanti; Azizah, Nur (Asian Journal of Social and Humanities, 2025)
Children with disabilities often experience low self-confidence problems due to their physical conditions, which impact their ability to socialize and interact with their environment. This study aims to analyze the influence of individual counseling techniques with a humanistic approach on increasing the self-confidence of children with disabilities at SMP Negeri 4 Sangatta Utara. The research method used was pre-experimental with a One Group Pre-Test – Post-Test Design. Data collection techniques used questionnaires with a Likert scale distributed to students with disabilities. Data were analyzed using SPSS through classical assumption tests (normality test, multicollinearity, and heteroscedasticity) and hypothesis testing (t-test and multiple linear regression). The results showed that individual counseling with a humanistic approach that includes empathy, unconditional positive regard, and genuineness has a significant effect on increasing the self-confidence of children with disabilities (sig. 0.023 < 0.05). The application of the humanistic approach in individual counseling proved effective in helping children with disabilities become more courageous to perform, optimistic, and not easily give up. This study concludes that individual counseling techniques with a humanistic approach can be used as an appropriate intervention to increase the self-confidence of children with disabilities.